2016
DOI: 10.1002/pc.24153
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, mechanical, and rheological properties of natural rubber/ethylene propylene diene monomer nanocomposites reinforced by multi‐wall carbon nanotubes

Abstract: Nanocomposites based on natural rubber (NR)/ethylene propylene diene monomer (EPDM)/multi‐wall carbon nanotubes (MWCNT) have been prepared in an internal and a two roll‐mill mixer in two steps. The effect of carbon nanotubes (MWCNTs) and rubber composition were studied on microstructure, mechanical and rheological properties of the vulcanizated NR/EPDM/MWCNT nanocomposites. Ethylene propylene diene monomer grafted with maleic anhydride (EPDM‐g‐MAH) was prepared using a solution process. Grafting of maleic anhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…These findings showed that elongation at the break of NR/SBR composites filled with 1.5 phr O-MWCNTs under optimized conditions was found to be 450% as compared to 376% for pristine NR/SBR composites. Nanocomposites based on NR/EPDM/MWCNT were also prepared in an internal and a two roll-mill mixer in two steps and effect of MWCNTs and studied for their mechanical properties [ 56 ].…”
Section: Mechanical Properties Of Rubber Nanocomposites Of Carbon mentioning
confidence: 99%
See 2 more Smart Citations
“…These findings showed that elongation at the break of NR/SBR composites filled with 1.5 phr O-MWCNTs under optimized conditions was found to be 450% as compared to 376% for pristine NR/SBR composites. Nanocomposites based on NR/EPDM/MWCNT were also prepared in an internal and a two roll-mill mixer in two steps and effect of MWCNTs and studied for their mechanical properties [ 56 ].…”
Section: Mechanical Properties Of Rubber Nanocomposites Of Carbon mentioning
confidence: 99%
“…Sui et al [ 47 ] observed that the storage modulus of the CNT/NR nanocomposites greatly exceeds that of neat NR and CB/NR composites. The glass transition temperature of natural rubber/ethylene propylene diene monomer nanocomposites slowly enhanced with increasing the contents of MWCNT [ 56 ]. Xu et al [ 32 ] performed dynamic mechanical measurements on NR/CB composite and NR/CB/MWCNTs composites with different MWCNTs loadings.…”
Section: Dynamical Mechanical Properties Of Carbon Nanofillers Conmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanocomposites based on NR/EPDM/MWCNT were prepared. in an internal and a two roll-mill mixer in two steps and effect of carbon nanotubes (MWCNTs) and mechanical properties of the vulcanized NR/EPDM/MWCNT nanocomposites [56].…”
Section: Mechanical Properties Of Carbon Filler Incorporated Sbr and mentioning
confidence: 99%
“…Razak et al have investigated the effect of graphene nanoplatelets on the processability and mechanical properties of NR/EPDM blends and found that the increase in graphene loadings promoted the processability by increasing the cure rate index and improved the tensile strength about twofold. Jahed et al studied the effect of CNTs and a compatibilizer such as EPDM grafted with maleic anhydride on the microstructure and mechanical properties of NR/EPDM with various blend ratios. They reported that the increase of CNTs up to 2 wt% leads to an increase in tensile strength and modulus at 300% elongation in the presence of EPDM grafted maleic anhydride.…”
Section: Introductionmentioning
confidence: 99%